2013
DOI: 10.1016/j.ijdevneu.2013.03.003
|View full text |Cite|
|
Sign up to set email alerts
|

Alterations in monoamines level in discrete brain regions and other peripheral tissues in young and adult male rats during experimental hyperthyroidism

Abstract: The present study was conducted to investigate the effect of experimentally-induced hyperthyroidism on dopamine (DA), norepinephrine (NE) and serotonin (5-HT) levels in different brain regions as well as in blood plasma, cardiac muscle and adrenal gland of young and adult male albino rats (60 rats of each age). Hyperthyroidism was induced by daily s.c. injection of L-thyroxine (L-T4, 500 μg/kg body wt.) for 21 consecutive days. Induction of hyperthyroidism caused a significant elevation in DA and 5-HT levels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 60 publications
2
13
0
Order By: Relevance
“…Mano [ 48 ] reported that the level of dopamine decreased significantly in hyperthyroidism. However, as Hassan [ 31 ] suggested, hyperthyroidism caused a marked elevation in dopamine level in various brain regions in an animal experiment. Because it is a controversial issue concerning the effect of hyperthyroidism on the level of dopamine in the brain from the previous literature, we speculated that impaired performance of the Stroop Color-Word Test and the IGT in patients with hyperthyroidism might be associated with dopamine dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Mano [ 48 ] reported that the level of dopamine decreased significantly in hyperthyroidism. However, as Hassan [ 31 ] suggested, hyperthyroidism caused a marked elevation in dopamine level in various brain regions in an animal experiment. Because it is a controversial issue concerning the effect of hyperthyroidism on the level of dopamine in the brain from the previous literature, we speculated that impaired performance of the Stroop Color-Word Test and the IGT in patients with hyperthyroidism might be associated with dopamine dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is known that intraperitoneal administration of T3 and T4 (for seven days) increased the number of cortical beta-adrenergic and serotoninergic receptors in adult rats [38]. Additionally, recent data suggest that iatrogenic hyperthyroidism in adult rats also changes the levels of dopamine, norepinephrine, and serotonin in different brain regions, as well as in blood plasma, cardiac muscle, and the adrenal glands [54]. All of these neurotransmitters play an important role in behavioral control.…”
Section: Endocrine Diseases and Behavioral Problemsmentioning
confidence: 99%
“…Further animal studies report an elevation in DA level after T4 injection [28,29] and vice versa, and a lower DA level in experimentally-induced hypothyroidism [30]. Hassan et al [29,30] have demonstrated an important role of T4 in the synthesis of DA. If there is too little T4 in the brain, insufficient DA can be synthesized or released, leading to more depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%